Giant magneto-photoelectric effect in suspended graphene - Jens Sonntag; Annika Kurzmann; Martin Geller; Friedemann Queisser; Axel Lorke; Ralf Schützhold (New Journal of Physics, 2017)
We study the optical response of a suspended, monolayer graphene field-effect transistor structure in magnetic fields of up to 9 T (quantum Hall regime). With an illumination power of only 3 μ W, we measure a photocurrent of up to 400 nA (without an applied bias) corresponding to a photo-responsivity of 0.13 A W ^−1 , which we believe to be one of the highest values ever measured in single-layer graphene. We discuss possible mechanisms for generating this strong photo-response (17 electron–hole pairs per 100 incident photons). Based on our experimental findings, we believe that the most likely scenario is a ballistic two-stage process including carrier multiplication via Auger-type inelastic Coulomb scattering at the graphene edge.